Confiança na Gestão Organizacional: os desafios da liderança nos tempos atuais - Drummond, Virginia Souza (2004)
Presents the results of theoretical and empirical studies based on the theories of Leadership, Trust, end Social Capital applied to the contemporary organizational scenario. The empiric research investigated psyco-sociological aspects undderlying leaders and managers practices in two private organizations, headquarttered in the city of Rio de Janeiro. The intensification of the competition in the contemporary globalized scenario has promoted accelerated changes and restructuring within organizations. Theses changes have created an atmosphere of internal instability and insecurity. In this context, the foundations for collective work have been threatened. Studies on organizational theory have also showed that trust is a fundamental issue in teh contemporary scenario, an issue that has placed the role of Leadership and Management under the spotlight. The responsability and importance, as well as the specific eays of performing this role, constituted the objective of the oresent work. The methodological approach adopted here was based on Lewin's conception of field and on the Theory os Social Representations, including the use of complementary qualitative and quantitative approaches. While taking into account the specificities of each organization taking part in the study, the use of comparative analyses revealed that specific formal leadership practices are still capable oh having a moderator effect on the creation of trustworthy environments, generating organizational social capital.